Apolipoprotein L-I promotes trypanosome lysis by forming pores in lysosomal membranes - NOLAN, DEREK (American Association for the Advancement of Science, 2005)
Apolipoprotein L-I is the trypanolytic factor of human serum. Here we show that this protein contains a membrane pore-forming domain functionally similar to that of bacterial colicins, flanked by a membrane-addressing domain. In lipid bilayer membranes, apolipoprotein L-I formed anion channels. In Trypanosoma brucei, apolipoprotein L-I was targeted to the lysosomal membrane and triggered depolarization of this membrane, continuous influx of chloride, and subsequent osmotic swelling of the lysosome until the trypanosome lysed.
PUBLISHED
Keywords: Biochemistry